Chilling stress response in tobacco seedlings: insights from transcriptome, proteome, and phosphoproteome analyses - Shao, Xiuhong; Zhang, Zhenchen; Yang, Faheng; Yu, Yongchao; Guo, Junjie; Li, Jiqin; Xu, Tingyu; Pan, Xiaoying (Frontiers in Plant Science, 2024)
Tobacco (Nicotiana tabacum L.) is an important industrial crop, which is sensitive to chilling stress. Tobacco seedlings that have been subjected to chilling stress readily flower early, which seriously affects the yield and quality of their leaves. Currently, there has been progress in elucidating the molecular mechanisms by which tobacco responds to chilling stress. However, little is known about the phosphorylation that is mediated by chilling. In this study, the transcriptome, proteome and phosphoproteome were analyzed to elucidate the mechanisms of the responses of tobacco shoot and root to chilling stress (4 ℃ for 24 h). A total of 6,113 differentially expressed genes (DEGs), 153 differentially expressed proteins (DEPs) and 345 differential phosphopeptides were identified in the shoot, and the corresponding numbers in the root were 6,394, 212 and 404, respectively. This study showed that the tobacco seedlings to 24 h of chilling stress primarily responded to this phenomenon by altering their levels of phosphopeptide abundance. Kyoto Encyclopedia of Genes and Genomes analyses revealed that starch and sucrose metabolism and endocytosis were the common pathways in the shoot and root at these levels. In addition, the differential phosphopeptide corresponding proteins were also significantly enriched in the pathways of photosynthesis-antenna proteins and carbon fixation in photosynthetic organisms in the shoot and arginine and proline metabolism, peroxisome and RNA transport in the root. These results suggest that phosphoproteins in these pathways play important roles in the response to chilling stress. Moreover, kinases and transcription factors (TFs) that respond to chilling at the levels of phosphorylation are also crucial for resistance to chilling in tobacco seedlings. The phosphorylation or dephosphorylation of kinases, such as CDPKs and RLKs; and TFs, including VIP1-like, ABI5-like protein 2, TCP7-like, WRKY 6-like, MYC2-like and CAMTA7 among others, may play essential roles in the transduction of tobacco chilling signal and the transcriptional regulation of the genes that respond to chilling stress.Taken together, these findings provide new insights into the molecular mechanisms and regulatory networks of the responses of tobacco to chilling stress.